A Qualitative Examination of Correctional Programming Perceptions and Experiences Among Incarcerated Women - Pederson, Kaitlyn M. (Crime & delinquency, 2024)
The rate at which women experience incarceration has increased substantially over the last four decades. Justice-involved women are often the primary caretakers of children and suffer more often from mental health, substance use, and other issues at higher rates than justice-involved males. Previous research has noted the need for gender-responsive programming, but less research has explored women inmate perceptions of the programming within women correctional facilities. This qualitative study examined 545 incarcerated women across multiple institutions in a large Southern prison system. We asked incarcerated women about their perceptions of accessibility, needs, benefits, and problems in correctional programming. Findings indicate that women?s programming may still not adequately address gender-based needs. Additionally, women among the sample identified several programming-related issues.